Cultural Rituals and Personal Mourning: A Comparative Analysis of Grief in The Book of Life and Manchester by the Sea - Pangaribuan, Anabelle Angelica Dora; Hapsarani, Dhita (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Although grief as a narrative trope is widely circulated in media intended for both children and adults, a gap remains in how contemporary grief models, particularly Continuing Bonds and the Dual Process Model, are represented in movies intended for different age groups. This study aims to provide insight into the differences and similarities in grief depictions in The Book of Life (2014) and Manchester by the Sea (2016) and whether these portrayals can be attributed to the intended age groups of the films, where the former is aimed at children and the latter is targeted toward general audiences. Using textual analysis, this research explores how contemporary grief theories manifest in the two films' narratives and cinematic elements, and the implications for the differing perspectives on grief. The findings reveal that while The Book of Life (2014) approaches grief symbolically by framing loss through communal rituals to offer hope amid loss, Manchester by the Sea (2016) presents grief as solitary and unresolved, highlighting emotional fracture and cultural complexities. Reading them together shows that the narratives of grief are shaped by cultural values and by assumptions about who the story is for.